(untitled) (Research, Society and Development, 2020)
Ecosystem services (SEs) are tangible and intangible goods produced by ecosystems that are used by society in pursuit of human well-being. Aquatic ecosystems provide crucial SEs, but by changing water quality and quantity, water bodies can alter the supply of these services. In this way, the present study aimed to classify the water SEs identified in a water source located in Belém-PA, evaluating how these SEs are impacted by the environmental pressures that act on these resources. The source object of this study consists of the lakes Água Preta and Bolonha, which is within the Utinga State Park (PEUt), an Integral Protection Conservation Unit that is inserted in the Belém Environmental Protection Area (APA Belém), and is responsible for the supply of drinking water to approximately 65% of the population of the Metropolitan Region of Belém (RMB). The research methodology was based on the scientific literature for theoretical approach to SEs and subsequent association with local environmental characteristics. Water supply, water regulation, self-cleaning, recreational and ecotourism and educational services were addressed. Finally, it was noticed that the various pressures on the source are related to changes in land use and cover in the areas adjacent to the lakes that compose it, mainly due to the expansion of urbanization, characterized by the dumping of sanitary sewage and sediments in lakes, resulting in the emergence of macrophytes, which in addition to changing the quality of the water of the spring, can contribute to its siltation.